Answer:
Thus, the two root of the given quadratic equation
is 2 and -3 .
Explanation:
Consider, the given Quadratic equation,
![x^2-6=-x](https://img.qammunity.org/2020/formulas/mathematics/high-school/hrdg8v1y6s51rlc4u05x4piu196z7ne175.png)
This can be written as ,
![x^2+x-6=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/lbzgixm6j3yicjzg49vicbv5w9nq5qslgq.png)
We have to solve using quadratic formula,
For a given quadratic equation
we can find roots using,
...........(1)
Where,
is the discriminant.
Here, a = 1 , b = 1 , c = -6
Substitute in (1) , we get,
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ty88pbafyv5o23b2f4dpdb7fqtzb1mmwac.png)
![\Rightarrow x=(-(1)\pm√((1)^2-4\cdot 1 \cdot (-6)))/(2 \cdot 1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/z4307diqkddp7khu1gs8cyog3em4dzz7ey.png)
![\Rightarrow x=(-1\pm√(25))/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4jyfbjpehdq1ow6txgn5sqccpa933y38gy.png)
![\Rightarrow x=(-1\pm 5)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/1dnydla0zqbn9b0h4snv18k2sw8d9k6qsd.png)
and
![\Rightarrow x_2=(-1-5)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/xk6nv8qx6i99gfv11s0imgg5nfpe1ps6g1.png)
and
![\Rightarrow x_2=(-6)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ymnag0gfdcr2xoiol4q9tins3n0jjidenq.png)
and
![\Rightarrow x_2=-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/yy1ax01dzpdwlf8t615iotsj297pm8pq1t.png)
Thus, the two root of the given quadratic equation
is 2 and -3 .